1994
DOI: 10.1115/1.2901570
|View full text |Cite
|
Sign up to set email alerts
|

Geometrically Nonlinear Stress-Deflection Relations for Thin Film/Substrate Systems With a Finite Element Comparison

Abstract: A new higher order geometrically nonlinear relation is developed to relate the deflection of a thin film /substrate system to the intrinsic film stress when these deflections are larger than the thickness of the substrate. Using the Rayleigh-Ritz method, these nonlinear relations are developed by approximating the out-of-plane deflections by a second-order polynomial and midplane normal strains by sixthorder polynomials. Several plate deflection configurations arise in an isotropic system: at very low intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…1). These values are compared in Table 1 with the analytical results of Masters and Salamon (1994) and Harper and Wu (1990). They are very close to those obtained by Masters and Salamon, in particular when computed at the quarter of the plate.…”
Section: Curvature Variation Along the Plate Axessupporting
confidence: 67%
See 2 more Smart Citations
“…1). These values are compared in Table 1 with the analytical results of Masters and Salamon (1994) and Harper and Wu (1990). They are very close to those obtained by Masters and Salamon, in particular when computed at the quarter of the plate.…”
Section: Curvature Variation Along the Plate Axessupporting
confidence: 67%
“…2), but leads to the perfectly symmetrical unstable one (curve BE). Consequently, a slight imperfection must be introduced to allow the system to converge towards one of the two stable solutions (Freund, 2000;Lee et al, 2001;Masters and Salamon, 1994). It is applied in the form of an anisotropic mismatch stress so that:…”
Section: Presentation Of Our Computationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Masters and Salamon [7] and Harper and Wu [8] used punctual curvatures measured in the center and at a quarter of the sample. Ngo et al [8] showed that the film stress depends on curvatures of the entire substrate and non-locally on the substrate curvature.…”
Section: Introductionmentioning
confidence: 99%
“…This crucial assumption is often violated in practice since film stresses and the associated system curvatures are nonuniformly distributed over the plate area [Masters and Salamon 1994]. Recently and relaxed the assumption (vi) (and also (iv) and (v)) to study the thin film/substrate system subject to nonuniform, Figure 1.…”
Section: Introductionmentioning
confidence: 99%